Cancer Treatment-Induced Bone Loss: Role of Denosumab in Non-Metastatic Breast Cancer - Dhabhar B (Breast Cancer: Targets and Therapy, 2022)
Boman Dhabhar Department of Medical Oncology, Fortis Hospital, Mumbai, IndiaCorrespondence: Boman Dhabhar, Consultant, Medical Oncology, Fortis Hospital, Mulund, Mumbai, 400078, Maharashtra, India, Email drboman@hotmail.comAbstract: Chemotherapeutic agents, endocrine therapy and radiotherapy used in the management of breast cancer are known to cause decreased bone mineral density, and thus, increased incidence of fractures. A majority (∼ 60%) of the breast cancer patients in India are either estrogen (ER) or progesterone hormone receptor (PR) positive. Adjuvant treatment with aromatase inhibitors (AIs) is the treatment mainstay for hormone-sensitive disease in postmenopausal (PM) women, with reduced bone mineral density (BMD), which results in increased fracture rates. Zoledronic acid, alendronate, risedronate and denosumab have been the agents of choice for managing bone loss. Denosumab 60 mg is approved for gaining bone mass in women with breast cancer who are at high risk for fracture following adjuvant AI treatment. The phase III HALT-BC data indicate an improvement in BMD with denosumab and a 50% reduction in clinical fractures, with significant improvements seen at the lumbar spine, distal third of the radius, and total hip. Denosumab has several advantages over other bone modifying agents such as subcutaneous self-administration by the patient themselves, no requirement of hospitalization, no dose modifications in renal impairment, and low incidence of acute phase anaphylactic reactions. We review the available evidence of denosumab for managing bone loss in non-metastatic breast cancer patients.Keywords: nonmetastatic breast cancer, postmenopausal women, denosumab, bone loss, bone mineral density, fracture